Ceppellini Lecture 2012: collateral damage from HLA mismatching in kidney transplantation - Opelz, Gerhard; Döhler, Bernd (Tissue antigens, 2013)
Inclusion of human leukocyte antigen (HLA) matching in donor kidney allocation schemes has been based solely on its association with graft survival. Other long-term effects associated with HLA incompatibility are largely unexplored. Data from deceased donor kidney transplants reported to the Collaborative Transplant Study have been analyzed to assess the relation between HLA mismatching and clinical events to 3 years post-transplant, and an overview of these analyses is presented. A significant correlation was observed between the number of mismatches and the need for anti-rejection therapy during the first year post-transplant, which was maintained for HLA-DR and HLA-A + B mismatching separately and at years 2 and 3 post-transplant. The number of HLA-DR mismatches and the number of HLA-A + B mismatches as well as rejection treatment showed significant associations with the dose of maintenance steroids. The cumulative incidences of death with a functioning graft from infection or cardiovascular causes, but not from cancer, were also significantly associated with HLA mismatching. The number of HLA-DR mismatches showed a significant association with the incidence of non-Hodgkin lymphoma and hip fractures. These findings show that the adverse consequences of HLA mismatching on kidney transplants extend beyond an effect on graft survival, and include an increased risk of death with a functioning graft, non-Hodgkin lymphoma and hip fracture.
Gesehen am 09.12.2021